Marital readiness: Exploring the key factors among university students - Danik Nur Fitria Ningrum; Melly Latifah; Diah Krisnatuti (HUMANITAS: Indonesian Psychological Journal, 2021)
Marital readiness, particularly in young adults, is an important aspect that will determine success in building a relationship with their spouse in the future. This study aimed to explore the key factors affecting marital readiness among university students. Critical factors included in this study design are age, family life preparation programs, emotional intelligence, and family life knowledge. A quantitative explanatory study with 120 university students in Jakarta Province as participants was conducted. Questionnaires consist of demographic data, family life knowledge, emotional intelligence, and marital readiness were used to collect the data. The data were then analyzed using PLS-SEM to determine the effect of the key factors on marital readiness. The results show that marital readiness is significantly influenced by age, involvement in family life preparation programs, family life knowledge, and emotional intelligence. Therefore, participating in family life preparation programs will enhance knowledge about preparing for family life, which will then increase marital readiness. Also, marital readiness will increase when university students have higher emotional intelligence and age.